Resposta :
Explicação passo-a-passo:
X²-2x -8 =0
a=1
b=-2
c=-8
∆=b²-4ac
∆=(-2)²-4*1*-8
∆=4+32
∆=36
-b±√∆/2a
2±√36/2*1
2±6/2
x¹=2+6/2=8/2=>4
x²=2-6/2=-4/2=>-2
X²+4x -12 =0
a=1
b=4
c=-12
∆=b²-4ac
∆=4²-4*1*-12
∆=16+48
∆=64
-b±√∆/2a
-4±√64/2*1
-4±8/2
x¹=-4+8/2=4/2=>2
x²=-4-8/2=-12/2=>-6
- X²+6x -8 =0
x²-6x+8=0
a=1
b=-6
c=8
∆=b²-4ac
∆=(-6)²-4*1*8
∆=36-32
∆=4
-b±√∆/2a
6±√4/2*1
6±2/2
x¹=6+2/2=8/2=>4
x²=6-2/2=4/2=>2
X²-5x +6
a=1
b=-5
c=6
∆=b²-4ac
∆=(-5)²-4*1*6
∆=25-24
∆=1
-b±√∆/2a
5±√1/2*1
5±1/2
x¹=5+1/2=6/2=>3
x²=5-1/2=4/2=>2
![Ver imagem LETICIA1618](https://pt-static.z-dn.net/files/dd7/6d3d9f1fae0f2788c53972d9cd366ec0.jpg)
![Ver imagem LETICIA1618](https://pt-static.z-dn.net/files/dfe/67bf011f4bc92eba966e2280bc9d1316.jpg)
![Ver imagem LETICIA1618](https://pt-static.z-dn.net/files/d7d/d287f101edc77d8cbbc26c8a6cb9d53f.jpg)
![Ver imagem LETICIA1618](https://pt-static.z-dn.net/files/d3c/ac5385c1cb9fecb5acc7d55fe2d93f6c.jpg)